Assessment of knowledge about epilepsy and attitude toward epilepsy among nurses in hospitals affiliated to Babol University of Medical Sciences - Masoud Pour Abbas (Romanian Journal of Neurology, 2019)
Background. The aim of this study was to determine the knowledge and attitude of nurses of hospitals affiliated to Babol University of medical sciences with regard to epilepsy and its related factors. Method. This descriptive study was performed on 500 nurses working at educational hospitals of Babol, Iran, in 2017. A questionnaire including 7 demographic questions, 14 questions of knowledge and 10 questions of attitude was used to collect the related data. Results were gained through ANOVA and T-test. Results. In this study, the level of knowledge about epilepsy was significantly higher in subjects younger than 25 years old (P = 0.03), but the attitude toward epilepsy across different age groups was not significantly different. Also, there was no significant difference between knowledge and attitude between the two sexes, marital status and work experience. Nurses’ knowledge was not significant in terms of education, but their attitude toward epilepsy was higher in those with undergraduate education than those with higher educated (P <0.001). There was no significant difference in knowledge about epilepsy based on income level, but their attitude was significantly higher in people with lower income (P <0.001). Conclusions. Nurses’ knowledge about epilepsy was higher in younger age groups and newly employed ones. Positive attitudes toward epilepsy also had a reverse relationship with education and income levels. A training program is needed to increase the awareness and skills of dealing with patients with epilepsy.